Pengaruh emotional intelligence terhadap organizational commitment melalui self efficacy - Djauhar, Roykhan El; Nugrohoseno, Dwiarko (Universitas Negeri Surabaya, 2024)
The primary purpose of this study is to investigate and assess the individual’s emotional intelligence impact on their organisational commitment, with a specific focus on examining the mediating role played by self-efficacy at PT. X. This research uses a quantitative approach. The sampling technique uses non-probability sampling with a saturation sample type, where all population members are used as samples, with 42 respondents from PT. X employees. The statistical analysis used is partial least square (PLS) with the help of SmartPLS 4.0 software. The findings of this study explain that organisational commitment is not influenced by emotional intelligence; emotional intelligence has a significant positive effect on self-efficacy, self-efficacy has a significant positive effect on organisational commitment, and emotional intelligence has a positive effect on organisational commitment mediated by self-efficacy. This study implies that enhancing self-efficacy can optimise employee emotional intelligence’s effect on their commitment to the organisation.